Against hybridity : social impasses in a globalizing world. - Hazan, Haim (Polity Press, 2015)
One of the major characteristics of our contemporary culture is a positive, almost banal, view of the transgression and disruption of cultural boundaries. Strangers, migrants and nomads are celebrated in our postmodern world of hybrids and cyborgs. But we pay a price for this celebration of hybridity: the non-hybrid figures in our societies are ignored, rejected, silenced or exterminated. This book tells the story of these non-hybrid figures Ð the anti-heroes of our pop culture.The main example of non-hybrids in an otherwise hybridized world is that of deep old age. Hazan shows how we fervently distance ourselves from old age by grading and sequencing it into stages such as 'the third age', 'the fourth age' and so on. Aging bodies are manipulated through anti-aging techniques until it is no longer possible to do it anymore, at which point they become un-transformable and non-marketable objects and hence commercially and socially invisible or masked. Other examples are used to elucidate the same cultural logic of the non-hybrid: pain, the Holocaust, autism, fundamentalism and corporeal death. On the face of it, these examples may seem to have nothing in common, but they all exemplify the same cultural logic of the non-hybrid and provoke similar reactions of criticism, terror, abhorrence and moral indignation.This highly original and iconoclastic book offers a fresh critique of contemporary Western culture by focusing on that which is perceived as its other Ð the non-hybrid in our midst, often rejected, ignored or silenced and deemed to be in need of globally manageable correction -- Présentation de l'éditeur.